2018
DOI: 10.3390/ijms19010088
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Plasma Proteome of Patients with Hypothyroidism before and after Thyroid Hormone Replacement: A Proteomic Analysis

Abstract: Thyroid hormone is a potent stimulator of metabolism, playing a critical role in regulating energy expenditure and in key physiological mechanisms, such as growth and development. Although administration of thyroid hormone in the form of levo thyroxine (l-thyroxine) has been used to treat hypothyroidism for many years, the precise molecular basis of its physiological actions remains uncertain. Our objective was to define the changes in circulating protein levels that characterize alterations in thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 53 publications
3
80
0
1
Order By: Relevance
“…the determination of TSH to monitor adequate secretion of TH. Despite the benefits of plasma proteomics, its application in biomarker research in general and thyroid research in particular is still limited (Geyer et al 2017, Alfadda et al 2018. The major challenge in plasma proteomics is the great dynamic range covering about ten orders of magnitude from highly abundant albumin (~0.6 mol/L) to low-abundant TSH (~5 pmol/L) (Hortin & Sviridov 2010).…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…the determination of TSH to monitor adequate secretion of TH. Despite the benefits of plasma proteomics, its application in biomarker research in general and thyroid research in particular is still limited (Geyer et al 2017, Alfadda et al 2018. The major challenge in plasma proteomics is the great dynamic range covering about ten orders of magnitude from highly abundant albumin (~0.6 mol/L) to low-abundant TSH (~5 pmol/L) (Hortin & Sviridov 2010).…”
Section: Proteomicsmentioning
confidence: 99%
“…However, a comparable study (Hooper et al 2012) observed no alterations in serum C3 levels (and coagulation factors) after 2 weeks of L-T 4 application. Moreover, endogenous hypothyroidism has been characterized by increased abundance of complement proteins using a plasma proteomic approach (Alfadda et al 2018). Hence, this seems to be a mid-to long-term effect with a U-shaped association with respect to the thyroid state.…”
Section: Proteomicsmentioning
confidence: 99%
“…None of the patients recruited in the study had a history of hypertension, diabetes mellitus, inflammatory or other autoimmune. Blood samples were collected after a standard 10 h fast by venipuncture into EDTA-coated tubes and plasma was obtained by centrifugation (15 min, 3000 × g), then was aliquoted and stored in multiple aliquots at -80°C until analysis [20].…”
Section: Study Design and Participant Selectionmentioning
confidence: 99%
“…DIGE analysis was performed to determine differentially expressed proteins between the hypothyroid Vs Euthyroid groups as described [20]. Briefly, Proteins extracted (50ug) from each sample were 6 labeled with either Cy3 or Cy5, respectively.…”
Section: D-dige and Maldi Tof/tof Ms Analysismentioning
confidence: 99%
See 1 more Smart Citation